Debates and controversies over the images of International News. Photo-impact on global front pages - Israel Garzón, Estrella (2013)
The journalistic images are subject to debate and controversy: from the girl of Trang Bang to the most recently images of women and female kids during the earthquake and the cholera epidemic in Haiti in 2010, comments on the symbolic and communicative value of the pictured subject keep occurring. The press images awarded as “photo of the year” by World Press Photo in the period between 2000 and 2011 represent international conflicts and disasters where the main characters are mostly women and children, plenty of drama and pathos. The axes of the discussion are the main photography situation on thedaily journal front page, against the right to privacy, the iconic representation of the sick people and victims of disasters and the social discussion through the network.